ANEMIA SEL SABIT - Suwiryawan, Gede Agus; Sutirta Yasa, I Wayan Putu; Dewi, DAP Rasmika (E-Jurnal Medika Udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Anemia is a form of blood disorder most often occurs in the community . Sickle cell anemia is anemia due to hemoglobinopathy caused by a change in the amino acid -6 of the ? globin chain . Sickle cell anemia is common in tropical areas of Africa and some parts of the region Saudi Arabia , India and the Mediterranean as well as black people in America. In addition there are also careers in various European countries . In pathophysiology , there are amino acid change from glutamic acid to valine in the ? -globin chain that causes red blood cells become sickle-shaped when deoxygenatied , but still be able to return to its normal shape when experiencing oxygenation . When the red blood cell membrane have been amended , the polymerization of red blood cells has become irreversible . Clinical picture seen in sickle cell anemia can be divided into two , namely: acute and chronic . Diagnosis can be done is to distinguish between heterozygous or homozygous sickle cell . T reatment provided in accordance with the clinical picture appears . Treatment that can be done is by blood transfusion , bone marrow transplant , anti - sickling drug delivery , and drug delivery to trigger the synthesis of HbF . Treatment still in the development stage is to use stem cells . /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Anemia, Sickle cell anemia, Hemoglobin